ASPEK-ASPEK FINANSIAL PENDIDIKAN ISLAM - Faisal Musa (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2021)
Islamic education is currently still faced with various fundamental problems. According to Siahaan, the low quality and quality of Islamic education, in general, is influenced by several factors, including the curriculum, facilities, graduates, teaching staff, and education funding. In some cases, madrasas and other Islamic educational institutions have not been able to outperform or balance the quality of school education in general. This paper will briefly explain the financial aspects of Islamic education as one of the dimensions or part of the Islamic education system, which is very important and affects the success and success of Islamic education in the future. Management or financial management regarding good planning, implementation, and evaluation will determine the success of education in achieving its goals. The number of funds obtained by an educational institution will not improve the quality and quality of education if it is not managed correctly according to the applicable rules and regulations. For this reason, apart from the availability of funds, human resources with integrity and competence are needed to manage and develop aspects of education financing.